ANALYSIS CODE-SWITCHING AND CODE-MIXING ON JEROME POLIN’S VIDEOS ON NIHONGO MANTAPPU’S YOUTUBE CHANNEL (SOCIOLINGUISTICS) - Nurul Zati Hanani; Raden Novitasari (WIDAI Japanese Journal, 2022)
The tittle of this research is "Analisis Alih Kode dan Campur Kode Pada Video Jerome Polin di Saluran Youtube Nihongo Mantappu (Kajian Sosiolinguistik)”. The purpose of this reasearch is to identify the types of code-switching and code-mixing used by Jerome Polin's video on Nihongo Mantappu's youtube channel. In this study, researcher implemented three videos of Jerome Polin on Nihongo Mantappu’s youtube channel as researched data. The code-switching theory used by Hoffman's theory and the code-mixing theory used by Muysken's theory. The method used in this research was descriptive qualitative with method consisting of three stages; the data collection stage, the data analysis stage and the presentation stage of data analysis results. The methods and techniques of data collection used in this research were listening to video downloaded from youtube. Researcher listened to the video repeatedly until found the code-switching and code-mixing in the conversation, then wrote in a notebook. The methods and techniques of data analysis used were intralingual method and determining element sorting technique. The method used in the presentation of data analysis results was an informal method. The results of this research showed that there were three types of code-switching; inter-centential (8 data), intra-centential (28 data) and emblematic / tag switching (6 data). And three types of code-mixing; insertion (17 data), alternation (5 data) and congruent lexicalization (10 data).